2017
DOI: 10.1002/anie.201700196
|View full text |Cite
|
Sign up to set email alerts
|

Next‐Generation Polymer Shells for Inorganic Nanoparticles are Highly Compact, Ultra‐Dense, and Long‐Lasting Cyclic Brushes

Abstract: Cyclic poly-2-ethyl-2-oxazoline (PEOXA) ligands for superparamagnetic Fe O nanoparticles (NPs) generate ultra-dense and highly compact shells, providing enhanced colloidal stability and bio-inertness in physiological media. When linear brush shells fail in providing colloidal stabilization to NPs, the cyclic ones assure long lasting dispersions. While the thermally induced dehydration of linear PEOXA shells cause irreversible aggregation of the NPs, the collapse and subsequent rehydration of similarly grafted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
99
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 40 publications
6
99
0
2
Order By: Relevance
“…Benetti and co‐workers found that small plasma proteins such as bovine serum albumin (BSA), can physisorb on linear brush shells composed of poly‐2‐ethyl‐2‐oxazoline (PEOXA). In contrast, the dense polymer shell was found to successfully provide enhanced long‐term stability and prevent the adsorption of proteins . Therefore, CBMA monomers polymerized into shells on nanoparticles may significantly improve the blood circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Benetti and co‐workers found that small plasma proteins such as bovine serum albumin (BSA), can physisorb on linear brush shells composed of poly‐2‐ethyl‐2‐oxazoline (PEOXA). In contrast, the dense polymer shell was found to successfully provide enhanced long‐term stability and prevent the adsorption of proteins . Therefore, CBMA monomers polymerized into shells on nanoparticles may significantly improve the blood circulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, HA/TB was stable in a PBS and bovine plasma solution, proven by the appearance of a main peak in the hydrodynamic size distribution, well maintained after 3 days at 37°C (Figure S2). [14] More importantly, no burst release of TB was found during incubation. The total TB released was minimal in both PBS and plasma (7.68% and 17.72% at day 3, Figure 1f).…”
mentioning
confidence: 99%
“…The present study provides an ovel design of smart switchable polyzwitterion based on aprecise control of the net charge.Thesurfaceofbiomaterialsdeterminestheir interaction with the surrounding biological substances.I np articular, nanomaterials for tumor-targeted therapy,l oading therapeutic molecules such as antitumor drugs and imaging agents, [1][2][3][4][5][6] have to avoid undesired interactions with blood components and normal tissues [7] until reaching the tumor sites; [8] the interactions are often associated with quick elimination from blood stream mostly based on the recognition by reticuloendothelial system (RES). The ethylenediamine moiety in the carboxybetaine enabled stepwise protonation and initiated the di-protonation process around tumorous pH (6.5).…”
mentioning
confidence: 99%